Given:
[tex]pV^{2}[/tex] = constant (1)
⇒ [tex]p_{1}V_{1}^{2} = p_{2}V_{2}^{2}[/tex] (2)
[tex]p_{1} = 1 bar = 1\times 10^{5}[/tex]
[tex]p_{2} = 9 bar = 9\times 10^{5}[/tex]
[tex]V_{1} = 0.4 m^{3}[/tex]
[tex]V_{2} = ? m^{3}[/tex]
Solution:
Here, from eqn (1), the polytropic constant is '2' ( Since, here [tex]pV^{n}[/tex] = [tex]pV^{2}[/tex] )
Now, using eqn (2), we get
[tex]V_{2}^{2} =\frac{p_{2}}{p_{1}}\times V_{1}^{2}[/tex]
putting the values in above eqn, we get-
[tex]V_{2}^{2} =\frac{9}{1}\times 0.4^{2}[/tex]
[tex]V_{2} = 1.2 m^{3}[/tex]
Now, work for the process is given by:
[tex]W = \frac{p_{2}V_{2} - p_{1}V_{1}}{1 - n}[/tex] (3)
where,
n = potropic constant = 2
Using Eqn (3), we get:
[tex]W = \frac{9\times 10^{5}\times 1.2 - 1\times 10^{5}\times 0.4}{1 - 2}[/tex]
W = - 240 kJ